2019
DOI: 10.3329/updcj.v9i1.41202
|View full text |Cite
|
Sign up to set email alerts
|

Causative Organisms of Hospital Acquired Infections Among The Pediatric Patients In Tertiary Level Hospitals of Dhaka City

Abstract: Hospital acquired infections (HAI) are important causes of morbidity and mortality. The purpose of this study was to see the type of HAI and causative organisms of these infections among the paediatric patients in tertiary level hospitals of Dhaka city. This cross sectional study was conducted in three tertiary level hospitals in Dhaka City over a period of two years. A total of 1055 patients were observed and the study population comprised of all the admitted paediatric patients irrespective of sex and basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another study reported that 2.6% of hospitalized patients and 4% of healthcare workers developed hospital-acquired diarrhea [ 12 ]. Other studies from Bangladesh have estimated overall rates of HAIs ranging from 8 to 30%, exacerbated by inadequate IPC [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that 2.6% of hospitalized patients and 4% of healthcare workers developed hospital-acquired diarrhea [ 12 ]. Other studies from Bangladesh have estimated overall rates of HAIs ranging from 8 to 30%, exacerbated by inadequate IPC [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Open access and overcome. 4 WHO and other health organisations have emphasised the importance of implementing effective infection prevention and control (IPC) programmes to curb the spread of these infections. These measures are critical to achieving sustainable development goals, improving patient safety and promoting universal health coverage.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Staphylococcus aureus (12.9%) and Pseudomonas aeruginosa (11.5%) are the most common pathogens implicated in HAIs. A study on post caesarean wound infection in Dhaka Medical College Hospital showed that 35.3% of caesarean patients developed hospital acquired infection 10 . A study on 299 admitted patients of Dhaka Medical College Hospital 34(11.37%) were found affected by HAI.…”
Section: Introductionmentioning
confidence: 99%